Parametric analysis of wing planforms to determine an optimal wing design - Manish Kumar Chauhan; Mayur Zope; Srinivasa Rao Gorrepati (Aviation)
In designing of Unmanned Aerial Vehicle (UAV), selection of an optimal wing design is a crucial part of complete UAV design process. This research explores the different aerodynamic parameters and the comparison of different wing planforms to ascertain the optimal wing design and improve the overall efficiency of an UAV. The computational analysis using XFLR5 and Open-VSP software is studied to investigate the various aerodynamic parameters of wing. The impact of aspect ratio, taper ratio, wing reference area, coefficient of lift and drag, and stall angle of attack are examined using the Analytical Hierarchy Process (AHP). The results emphasize the importance of different wing planforms and create easier selection of planform for the UAV designers. The study does not only provide the values for operating parameters but also offers practical guidance for design optimization. The semi tapered, and moderate tapered (λ = 0.5) wings are the good choice to select at the initial phase of design. The highly tapered and elliptical wings provide higher lift but are not efficient in the stalling conditions. Furthermore, the rectangular wing provides elliptical lift distribution, but it is inefficient in the lift generation.